The Future of Indonesian Education: Transformation Towards the Industrial Era 4.0 and Society 5.0 - Vanditta, Ryni; Pramono, Suwito Eko; Yulianto, Arief (Universitas Negeri Semarang, 2025)
The development of Industry 4.0 and Society 5.0 has brought significant transformations in various sectors, including education. This change is characterized by the integration of advanced technologies such as artificial intelligence (AI), the Internet of Things (IoT), and big data that are changing the way we learn, work, and interact. However, Indonesia still faces challenges such as the digital divide, low technology literacy, and limited educational infrastructure, which require innovative solutions. This research discusses research questions on how education in Indonesia can adapt and take advantage of existing opportunities to create a technologically competent generation while maintaining character and upholding human values. Using a qualitative descriptive method based on literature analysis, this study aims to identify challenges, opportunities, and strategies for education transformation that are relevant in this era. The results of the study show that curriculum transformation, teacher training, and infrastructure strengthening are strategic steps to create inclusive, adaptive, and competitive education. The benefit of this research is to provide strategic guidance for policymakers, educators, and education practitioners in developing education systems that are relevant, responsive to global challenges, and able to empower the younger generation to contribute positively in the digital era.